The Impact of Authenticity in Key Opinion Leaders Branding Communication - Setiawati, Isti Budhi; Novrianto , L.M. (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This study aims to analyze the role of authenticity in branding communication conducted by Key Opinion Leaders (KOLs) and its impact on consumer trust, emotional engagement, and brand loyalty. Employing a library research approach, data were collected from scholarly literature published between 2021 and 2025 relevant to authenticity, brand communication, and KOL-based marketing. The analysis reveals that authenticity serves as a key element linking brand values to positive audience perceptions, which subsequently influence brand equity and purchase intention. Furthermore, this research highlights that authenticity in digital marketing is not merely a rhetorical claim but a relational practice that shapes how consumers evaluate credibility and trustworthiness. Strategic communication practices such as narrative storytelling, transparent sponsorship disclosure, and value alignment significantly strengthen the credibility of both KOLs and the brands they represent. Authentic storytelling allows audiences to connect with the personal experiences of KOLs, thereby enhancing identification and fostering long-term engagement with the brand. However, this study also identifies several challenges in maintaining authenticity, including risks of over-commercialization, inconsistencies in message delivery, and misalignment between KOL identity and brand values. When audiences perceive exaggerated promotional tactics or lack of transparency, their trust can diminish, ultimately weakening brand loyalty. Therefore, the sustainability of authenticity requires continuous monitoring, adaptive strategies, and consistent ethical practices in brand communication. The findings affirm that authenticity is both a strategic differentiator and a fragile asset, requiring deliberate and sustained management in the competitive digital marketplace. By recognizing authenticity as a multidimensional construct—encompassing transparency, value congruence, and emotional resonance—brands and KOLs can collaboratively enhance audience engagement while preserving credibility. This research contributes to the development of more effective branding communication strategies through KOLs and offers practical guidance for marketers to navigate authenticity challenges in an era dominated by digital interactions and consumer skepticism.